Pengertian dan Ruang Lingkup Musytaraq Al Lafzi, Ta'addud Al Ma'na serta Taraduf dalam Kajian Ilmu Dalalah - Mukhlis, M. Hasbi; Hidayat, Nandang Sarip (Journal of Practice Learning and Educational Development, 2024)
This research aims to describe and explain the theories of musytaraq al lafzi, ta’addud al ma’na, and taraduf within the discipline of semantics or dalalah in the study of Arabic linguistics, using library research as the data source. (library research).Various expressions in the study of the Arabic language are found to have their own unique characteristics and are interesting to study in depth. The relationships between meanings, such as those in modern linguistics called synonymy, polysemy, homonymy, and antonymy, are all found in Arabic linguistics and are also frequently encountered in the language of the  Al Quran. The results of this research indicate that there are words with one term and multiple meanings, and there are also terms with multiple words and one meaning. Additionally, there are words and meanings that contradict each other, which are referred to in this context as mustaraq al lafzi, taraduf/muradif, and tudaad. Related to the position of Arabic as the language of the  Al Qur'an, the existence of musyataraq al lafz, taadud al makna, and taraduf also affects its translation and interpretation. The existence of patterns included in the study of the science of dalalah in the Al Qur'an is one of the proofs that the Al Qur'an possesses advantages and uniqueness in terms of language, known as I’jazul Al Lughawi.